MECHANISMS ENSURING SUSTAINABLE SOCIAL AND ECONOMIC DEVELOPMENT OF REGIONS - Liubov N. Orlova (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
The article deals with investigation and grounding the possibility of using relevant mechanisms and tools to pursue policy of sustainable social and economic development of regions in the Russian Federation. From the theoretical and methodological point of view the research presents criteria for substantiation of relevance degree: principles of pursuing policy of sustainable social and economic development (systematic and complex nature, keeping the balance of interests, taking into account continuous changes); typology of Russian Federation regions (locomotives of growth, support regions, depressive regions); scenarios and factors of regions’ strategic development according to the forecast of the long-term social and economic development of the Russian Federation. From the practical point of view the matrix of mechanisms ensuring sustainable social and economic development was designed, on the basis of which it is possible to choose and apply relevant organizational-managerial tools with regard to specificities of social and economic development of the territory.